The impact of maternal smoking during pregnancy on early child neurodevelopment - Wehby, George L. (2011)
Early child neurodevelopment has major impacts on future human capital and health. However, not much is known about the impacts of prenatal risk factors on child neurodevelopment. We evaluate the effects of maternal smoking during pregnancy on child neurodevelopment between 3 months and 24 months of age and interactions with socioeconomic status (SES). We employ data from a unique sample of children from South America. Smoking has large adverse effects on neurodevelopment, with larger effects in the low-SES sample. Our results highlight the importance of early interventions beginning before and during pregnancy for enhancing child development and future human capital attainment.